Eliminate angular color shift in top‐emitting OLEDs through cavity design. Issue 8 (30th May 2019) - Dong, Chen; Fu, Xiangyu; Amoah, Stephen; Rozelle, Adam; Shin, Dong‐Hun; Salehi, Amin; Mendes, Juliana; So, Franky
Abstract: OLEDs suffer from viewing angle dependent spectral shift due to microcavity effects. To address this issue, we introduce a novel top‐emitting OLED with a dielectric spacer that forms multiple cavity modes. The resulting device shows almost no color shift at different viewing angles. Abstract : A multi‐mode top‐emitting OLED having an 8.5‐μm dielectric spacer with a metal reflector is proposed. This structure induces multi‐mode effect and eliminates the spectrum shift with viewing angles caused by the single microcavity.